1D infiltration behavior of two-layered recycled concrete aggregates using hydrophobic materials in a column apparatus - Rahardjo H.; Prasad A.; Satyanaga A.; Mohamed H.; Leong E.-C.; Wang C.-L.; Wong J.L.-H. (My University, 2025)
The infiltration characteristics of two different hydrophobic materials were investigated in this study. The materials used in this study were fine and coarse recycled concrete aggregates (RCA). One-dimensional (1D) vertical infiltration column tests were carried out on fine RCA over coarse RCA, fine RCA over coarse RCA with oil, and fine RCA over coarse RCA with wax. The column apparatus were instrumented with a tensiometer-transducer system, data acquisition system, soil moisture sensor, and electronic weighing balance. The comprehensive instruments were used to measure pore-water pressure, water content, and outflow rate of water instantaneously and automatically. The experimental results indicated that the water flowed faster within the layer of coarse RCA with oil and wax as compared to that within the layer of coarse RCA without oil and wax. This could be attributed to the hydrophobicity of each solid particle of coarse RCA that was coated with oil and wax. © 2017 American Society of Civil Engineers.